2022
DOI: 10.1002/prp2.977
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue‐derived stem cells as a potential candidate in treatment of Alzheimer's disease: A systematic review on preclinical studies

Abstract: In recent years, numerous investigations have evaluated the efficacy of adipose tissue‐derived stem cells (ADSCs) and their exosome transplantation in managing Alzheimer's disease (AD) in different animal models. However, there are still many contradictions among the studies that hinder reaching a reliable conclusion. Therefore, we aimed to systematically review the existing evidence regarding the efficacy of ADSCs administration in treatment of AD. The systematic search was conducted in the databases of Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The pro-inflammatory ADSCs can increase neuroinflammation by inducing proliferation and differentiation of CD4+ and CD8+ T cells [ 17 ]. Transplantation of ADSCs into a rat model of AD ameliorates cognitive impairments, enhances Aβ clearance, and suppresses apoptosis and neuroinflammation by modulating central and systemic SIRT1 levels [ 18 , 19 ]. Intraventricular injection of ADSCs has been shown to improve AD pathogenesis by modulating central cholesterol homeostasis [ 20 ].…”
Section: Remodeling Of Adipose Tissue Shapes Cognitive Functionmentioning
confidence: 99%
“…The pro-inflammatory ADSCs can increase neuroinflammation by inducing proliferation and differentiation of CD4+ and CD8+ T cells [ 17 ]. Transplantation of ADSCs into a rat model of AD ameliorates cognitive impairments, enhances Aβ clearance, and suppresses apoptosis and neuroinflammation by modulating central and systemic SIRT1 levels [ 18 , 19 ]. Intraventricular injection of ADSCs has been shown to improve AD pathogenesis by modulating central cholesterol homeostasis [ 20 ].…”
Section: Remodeling Of Adipose Tissue Shapes Cognitive Functionmentioning
confidence: 99%
“…[33][34][35] A growing body of evidence has shown that Ad-MSCs exhibit potential beneficial impact in the rescue of AD, particularly through reducing the size of Aβ plaques and mitigation of cognitive decline. 36 In fact, Ad-MSCs have been reported to mediate their actions through various mechanisms, including their immunomodulatory abilities, tissue regenerative capacity, and most importantly via the secretion of various cytokines, growth factors, and extracellular vesicles which employ various bioactive mediators, immunomodulatory, and anti-inflammatory molecules. 22,[37][38][39][40] Yet, further research is warranted to fully elucidate the molecular factors that mediate their various therapeutic beneficial effects in the context of different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there has been a surge in the use of Ad‐MSCs in the treatment of different neurodegenerative disorders 33–35 . A growing body of evidence has shown that Ad‐MSCs exhibit potential beneficial impact in the rescue of AD, particularly through reducing the size of Aβ plaques and mitigation of cognitive decline 36 . In fact, Ad‐MSCs have been reported to mediate their actions through various mechanisms, including their immunomodulatory abilities, tissue regenerative capacity, and most importantly via the secretion of various cytokines, growth factors, and extracellular vesicles which employ various bioactive mediators, immunomodulatory, and anti‐inflammatory molecules 22,37–40 .…”
Section: Introductionmentioning
confidence: 99%